Legionella pneumophila subverts the antioxidant defenses of its amoeba host Acanthamoeba castellanii - Alban Hay; Willy Aucher; Romain Pigeault; Joanne Bertaux; Alexandre Crépin; Quentin Blancart Remaury; Yann Héchard; Ascel Samba-Louaka; Romain Villéger (Current Research in Microbial Sciences)
Legionella pneumophila, the causative agent of Legionnaires' disease, interacts in the environment with free-living amoebae that serve as replicative niches for the bacteria. Among these amoebae, Acanthamoeba castellanii is a natural host in water networks and a model commonly used to study the interaction between L. pneumophila and its host. However, certain crucial aspects of this interaction remain unclear. One such aspect is the role of oxidative stress, with studies focusing on reactive oxygen species (ROS) production by the host and putting less emphasis on the involvement of the host's antioxidant defenses during the infectious process. In this study, we propose to examine the consequences of infection with L. pneumophila wild-type or with an isogenic ΔdotA mutant strain, which is unable to replicate intracellularly, on A. castellanii. For this purpose, we looked at the host ROS levels, host antioxidant defense transcripts, and metabolites linked to the amoeba's antioxidant defenses. It is known that L. pneumophila WT can block the activation of NADPH oxidase as soon as it enters the macrophage and suppress ROS production compared to ΔdotA mutant strain. In addition, it has been shown in macrophages that L. pneumophila WT decreases ROS at 24 h p.i.; here we confirm this result in amoebae and suggest that this decrease could be partly explained by L. pneumophila differentially regulated host antioxidant defense transcripts at 6 h p.i.. We also explored the metabolome of A. castellanii infected or not with L. pneumophila. Among the 617 metabolites identified, four with reduced abundances during infection may be involved in antioxidant responses. This study suggests that L. pneumophila could hijack the host's antioxidant defenses during its replication to maintain a reduced level of ROS.